PENGEMBANGAN MEDIA BOARD GAME MONOPOLI PADA MATA PELAJARAN INFORMATIKA MATERI SISTEM KOMPUTER KELAS X - Nabila Putri, Ahnaf; Augrah, Septriyan; Kurnia, Reni; Alfahani, Khairul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the use conventional media such as textbooks and presentation slides in Informatics learning at grade X of SMAS Adabiah 2 Padang, which have been unable to encourage active student engagement. A survey of 62 grade X students revealed that 71% preffered learning through educational games, while limited acces to the internet and further hindered optimal technology-based learning. This study aimed to develop a Monopoly board game learning medium on the Computer Systems topic in grade X Informatics that is valid, practical, and effective for use in the learning procces. The research employed as a Researche and Development (R&D) method using the ADDIE model, convering the stages of Analyze, Design, Development, Implementation, and Evaluation. The resulting product is a Monopoly board game equipped with individual and collaboration question card, asset card, a game board, and a playing guide, all aligned with the Learning Outcomes and Learning Objectives. Validity testing yielded score of 80% on the material aspect (Valid), and an average 94,7% on the media aspect (Very Valid). Practicality testing produced scores of 89% from teachers and 82,4% from student, both classified as Very Practical. Effectiveness testing using the N-gain score generated an average of 69,33%, categorized as Sufficiently Efective in improving student’s cognitive outcomes. These results indicate that the developed medium meets the criteria of valid, practical, and effective, making it suitable for use as a supporting learning medium for Informatics on the Computer Systems topic in grade X of senior high school.